Electronic Assessment Design Integrated Critical Thinking Skills Education for Sustainable Development on Motion Kinematics Material - Imrahatul Husna Junaida; Emiliannur Emiliannur; Hamdi Hamdi; Dea Stivani Suherman (Journal of Innovative Physics Teaching, 2026)
Ideally, physics education in the 21st century should develop students’ critical thinking skills to address global sustainability challenges. However, current physics assessment practices often do not effectively foster these skills and remain insufficiently integrated with the principles of Education for Sustainable Development (ESD). This study aimed to analyze the need for and develop an electronic assessment integrating critical thinking skills within ESD-based kinematics learning. The research employed a Research and Development (R&D) approach using the 4D model up to the development stage. The participants were 26 eleventh-grade students from SMAN 3 Pariaman. Data were collected through critical thinking tests based on Facione’s indicators, questionnaires, and interviews. The results showed that students’ critical thinking skills were relatively low, particularly in the evaluation aspect, which obtained the lowest score of 30.76%. In addition, ESD integration in assessment practices was still limited. Students’ preference for visual and auditory learning styles indicates the potential effectiveness of digital assessments. Therefore, developing an electronic assessment integrating critical thinking and ESD principles is necessary to support meaningful and sustainability-oriented physics learning.